A Budapesti Közlekedési Szövetség területén várható demográfiai kihívások - L. Rédei, Mária (Közép-Európai Közlemények, 2009)
The surrounds of Budapest have been in the focus of development attention. The actuality of the paper is the turning point of population development of capital and agglomeration after the suburbanisation period it is expected to verify the first sign of dezurbanisation. The aim of this paper is to map the current demographic situation on small territorial level and to give a prognosis up to 2036. Probably the spatial distribution of foreign population creates high interest towards the management of mobility, which is highly related to the future expectation. The international migration is the balance of stable population. The spatial analysis of international flow by different arguments is able to put forward the regional strategy of movement. The regional actor plays a determining contribution in integration of foreigners. The stock of foreign n population is the top in the country in Budapest agglomeration. It is a great challenge for the capital to integrate inhabitants by different culture, skill and social value. Although the initiatives of this estimation based on demography techniques, but the output is related to economical and infrastructural strategy.